The students creative thinking on environmental pollution material using video-assisted problem based learning model - Nyoman Trijaya Kusuma; Dina Maulina; Wisnu Juli Wiyono (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
The ability to think creatively has an important role in 21st century learning. This study aims to determine the effect of applying the video-assisted Problem Based Learning (PBL) model on the creative thinking skills of class VII students of SMP Negeri 1 Sekampung Udik on environmental pollution material. The research sample was selected by purposive sampling technique. The design of this study used a quasi-experimental design with a non-equivalent control group design. The type of data taken is quantitative data and qualitative data. Quantitative data in the form of mean values of pretest, posttest, and N-gain ability to think creatively tested using the Independent Sample t-Test with a significance level of 5% obtained Sig. (2-tailed) 0.00 <0.05. Qualitative data in the form of a questionnaire on student responses to the use of the video-assisted PBL model. The results showed that the N-gain value for the experimental class was 0.57 in the